The Analysis of Bottle Warehouse Facility Layout Design Using the System Layout Planning Method (SLP) Using Software Craft In PT.XYZ - Nugraha, Nayandra Agustira; Widjajati, Endang Pudji (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Increasingly advanced industry and increasingly fierce business competition encourage companies to improve employee work output and supporting facilities, including warehouses. PT. XYZ, a bottled water manufacturing company, is facing inefficiencies in its bottle warehouse. The initial layout was not optimal, with less than optimal space utilization and high moving costs. This causes obstruction to the smooth flow of materials and products, as well as reduced productivity. This research aims to redesign the layout of PT's bottle warehouse facilities. Atlantic Biruraya uses the Systematic Layout Planning (SLP) method to maximize productivity. The SLP method was used to redesign the layout of the bottle warehouse by considering factors such as material flow, space requirements and efficiency. Data was collected through observation, interviews and literature study. Data were analyzed using SLP software. The research results show that the new layout can increase productivity by reducing total costs by IDR 90.439. With the results of the proposed layout that has been created using craft software, the company can maximize productivity because the costs and distances required have been optimized using the Layout Planning System method using craft software.